Erratum: Studies on H2-assisted liquefied petroleum gas reduction of NO over Ag/Al2O3 catalyst (Bulletin of Chemical Reaction Engineering & Catalysis (2018) 13:2 (227-235) DOI: 10.9767/bcrec.13.2.1307.227-235) - Singh P.; Yadav D.; Thakur P.; Pandey J.; Prasad R. (My University, 2025)
An error appeared in Corresponding Author in a paper entitled “Studies on H2-Assisted Liquefied Petroleum Gas Reduction of NO over Ag/Al2O3 Catalyst” published in Bulletin of Chemical Reaction Engineering & Catalysis. The Corresponding Author is corrected to be: * Corresponding Authors. Tel: +919415268192. Email: rprasad.che@itbhu.ac.in (R. Prasad) Tel: +917505072607. Email: dyadav.rs.che13@iitbhu.ac.in (D. Yadav). © 2020 BCREC Group. All rights reserved